A narrative perspective of island detection methods under the lens of cyber-attack in data-driven smart grid - Apoorva Shukla; Soham Dutta; Sourav Kumar Sahu; Pradip Kumar Sadhu (Journal of Electrical Systems and Information Technology, 2023)
Abstract As criminals and hackers are developing new methods to interfere with the operation of the power grid, the nature of grid vulnerabilities and threats is continuously evolving. The growing interest in transitioning the unidirectional power system to a bidirectional data-driven modern grid will further escalate these issues. The question of cyber security becomes essential in particular critical decisions such as island detection. The incorrect decision of island occurrence may completely disrupt the operation of a portion of the grid, causing substantial damage to electrical equipment and grid maintenance workers. Fast monitoring and accurate control of unplanned islanding detection are essential for distributed generation-based active networks for providing continuous power supply to critical loads. Considering the above aspects, this paper serves on the perspective of different island detection methods and various aspects of cyber security. The type of cyber-attacks is categorized in terms of their behavior. Key points are discussed about how, when, and in what fashion and degree it can harm all the sectors of the grid, i.e., generation, transmission, and distribution system. Finally, the impact of cyber-physical attacks on the islanding decision system is presented. The research remedies for such measures are also presented. Moreover, a comparison is being made among various island detection methods based on the extent of impact of different cyber-attacks on the operation of these methods. Some promising future solutions for cyber-secure island detection methods are also suggested.